Effect of Methanol Leaf Extract of Annona senegalensis on Liver Function in Diethylnitrosamine-Induced Hepatocellular Carcinoma in Rats and Its Potential as an Antibacterial Agent - Umaru, Isaac John; Udoh, Mary Athanasius; Mona, Etah Hope; Omolara, Mosugu Ovayoza; Okang, Ogar Fonne; Akem, Ingwu Joseph; Tansaba, Akafa Andes; Philip, Shadrach; Frank, Otashu Kenneth (Darul Yasin Al Sys, 2025)
Hepatocellular carcinoma (HCC) is among the most prevalent and deadly cancers globally, with limited treatment options and poor prognosis in advanced stages. This study evaluated the therapeutic potential of methanol leaf extract of Annona senegalensis against diethylnitrosamine (DEN)-induced HCC in Wistar rats and investigated its antibacterial properties. Thirty-six male albino rats were allocated into six groups: Group I (normal control) received no treatment; Group II (negative control) was induced with HCC using DEN (50 mg/kg b.w., intraperitoneally) weekly for three weeks without therapy; Group III (positive control) received DEN followed by silymarin (100 mg/kg b.w.); while Groups IV, V, and VI received DEN followed by A. senegalensis extract at 200, 400, and 600 mg/kg b.w., respectively, administered orally for 14 days. Biochemical analysis showed that the extract significantly (p < 0.05) ameliorated DEN-induced hepatotoxicity, with the 400 mg/kg dose most effective in reducing AST (48.71 ± 1.21 IU/L) and ALT (20.74 ± 1.06 IU/L) compared to the negative control (69.52 ± 0.88 IU/L and 54.97 ± 1.54 IU/L, respectively). Hepatic synthetic function was restored, as indicated by increased total protein (6.37 ± 0.13 g/L) and albumin (5.11 ± 0.10 g/L). Histopathological analysis confirmed marked architectural recovery with reduced necrosis and inflammatory infiltration. The extract also demonstrated significant antibacterial activity, exhibiting dose-dependent inhibition zones against Gram-positive (Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacteria, with effects comparable to standard antibiotics. These findings suggest that A. senegalensis leaf extract exerts hepatoprotective effects—likely through antioxidant, anti-inflammatory, and antiproliferative mechanisms—while also offering broad-spectrum antimicrobial benefits. The 400 mg/kg dose emerged as the most effective, highlighting its promise as a cost-effective complementary therapy for managing HCC and bacterial infections, particularly in resource-constrained settings. Further research should focus on isolating and characterizing the bioactive compounds and elucidating their mechanisms of action.